2023
DOI: 10.1001/jamanetworkopen.2023.35715
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use and Sustained Virologic Response to Hepatitis C Virus Direct-Acting Antiviral Therapy

Emily J. Cartwright,
Chloe Pierret,
Caroline Minassian
et al.

Abstract: ImportanceSome payers and clinicians require alcohol abstinence to receive direct-acting antiviral (DAA) therapy for chronic hepatitis C virus (HCV) infection.ObjectiveTo evaluate whether alcohol use at DAA treatment initiation is associated with decreased likelihood of sustained virologic response (SVR).Design, Setting, and ParticipantsThis retrospective cohort study used electronic health records from the US Department of Veterans Affairs (VA), the largest integrated national health care system that provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
0
0
0
Order By: Relevance
“…However, reductions in administrative barriers (eg, requirements around minimum time in remission from substance use, minimum fibrosis scores, etc) have increased treatment accessibility across the United States. Research has demonstrated high rates of treatment adherence and sustained virologic response (SVR) in patients with active substance use, 14 including AUD 15 and low reinfection rates 16 . HCV treatment outcomes have also been found to be similar among PWUD with and without IDU 17 .…”
Section: Hcv Care Among Individuals With Sudmentioning
confidence: 99%
“…However, reductions in administrative barriers (eg, requirements around minimum time in remission from substance use, minimum fibrosis scores, etc) have increased treatment accessibility across the United States. Research has demonstrated high rates of treatment adherence and sustained virologic response (SVR) in patients with active substance use, 14 including AUD 15 and low reinfection rates 16 . HCV treatment outcomes have also been found to be similar among PWUD with and without IDU 17 .…”
Section: Hcv Care Among Individuals With Sudmentioning
confidence: 99%